Exploring career experiences of Swedish professional handball players: Consolidating first-hand information into an empirical career model - Ekengren, J.; Stambulova, N.; Johnson, U.; Carlsson, I.-M. (International Journal of Sport and Exercise Psychology, 2020)
The study was aimed at developing the empirical career model of Swedish professional handball players by means of exploring their career experiences in athletic and non-athletic developments through the lens of the holistic athletic career model. Eighteen Swedish professional handball players (nine men and nine women), who had recently terminated or were finishing their careers took part in semi-structured interviews about their careers from the beginning to the end with an interest in both athletic and non-athletic developments. Thematic analysis initially focused on identifying the handball career structure (i.e. stages and sub-stages). Then, the interviews were analysed inductively to identify shared themes in the players` experiences relevant to each career stage. These themes were incorporated in the relevant stages, and the empirical career model of Swedish professional handball players (further - the empirical model) was finalised. The empirical model describes careers of Swedish handball players as having four athletic stages - initiation, development (with three sub-stages), mastery (with four sub-stages), and discontinuation - complemented by players` psychological, psychosocial, academic/vocational, and financial developments. Each stage is also aligned with age markers and contains themes describing players` career experiences from the holistic perspective. The empirical model contributes to contextualised career research and serves as a basis for developing career-long psychological support services in Swedish handball including player/coach/parent education organised by the Swedish Handball Federation.